Role of Puffed Cheek Multi Detector Computed Tomography in The Evaluation and Extension of Gingivo-Buccal Carcinoma (KYAMC Journal, 2025)
Background: In our country oral cancer is a frequent cancer, people usually affected by this cancer are of older age. Accurate evaluation of this cancer is difficult due to its close proximity to  bones and soft tissue, but extension of the lesion can be evaluated by MDCT. Objective: To determine the extension and spread of buccal mucosal lesion, multi-detector Computed Tomography (MDCT) is an appropriate imaging modality of choice, findings  allow the radiologist to accurately determine the extent and staging of disease thereby help clinicians plan appropriate treatment. Materials and Methods:  Retrospective study of 50 patients who underwent MDCT and were histopathogically proven case of squamous cell carcinoma (SCC) of buccal mucosa  were included in the study from the time period 2022(January) to 2023(July) conducted in Radiology and Imaging department of Khwaja Yunus Ali Medical College and Hospital. After meeting the inclusion criteria patients were underwent for CT scan. Imaging was performed from paranasal sinus and neck region with axial sections from pituitary fossa to arch of aorta, after injection of intravenous iodinated contrast media, multiplanar sagittal, coronal reformation images were obtained. Results: Majority of them were female  (30) as compared to male (20). Among these 50 patients, 22 were classified as stage IVA with extension into masticator space. It was followed by stage IVB 20, stage III 6 and stage II 2. No patient having stage I cancer was found in this study. Conclusion: Cancer of the buccal mucosa has the potential to spread both deeply and superficially to various parts of the oral cavity and nearby structures. MDCT could outline their stages and spread patterns, so can assist clinicians in making their right plan.